A High-Throughput Screen to Identify LRRK2 Kinase Inhibitors for the Treatment of Parkinson's Disease Using RapidFire Mass Spectrometry. (February 2016) - Leveridge, Melanie; Collier, Lee; Edge, Colin; Hardwicke, Phil; Leavens, Bill; Ratcliffe, Steve; Rees, Mike; Stasi, Luigi Piero; Nadin, Alan; Reith, Alastair D.
LRRK2 is a large multidomain protein containing two functional enzymatic domains: a GTPase domain and a protein kinase domain. Dominant coding mutations in the LRRK2 protein are associated with Parkinson's disease (PD). Among such pathogenic mutations, Gly2019Ser mutation in the LRRK2 kinase domain is the most frequent cause of familial PD in Caucasians and is also found in some apparently sporadic PD cases. This mutation results in 2- to 3-fold elevated LRRK2 kinase activity compared with wild type, providing a clear clinical hypothesis for the application of kinase inhibitors in the treatment of this disease. To date, reported screening assays for LRRK2 have been based on detection of labeled adenosine triphosphate and adenosine diphosphate or on antibody-based detection of phosphorylation events. While these assays do offer a high-throughput method of monitoring LRRK2 kinase activity, they are prone to interference from autofluorescent compounds and nonspecific events. Here we describe a label-free assay for LRRK2 kinase activity using the RapidFire mass spectrometry system. This assay format was found to be highly robust and enabled a screen of 100, 000 lead-like small molecules. The assay successfully identified a number of known LRRK2 chemotypes that met stringent physicochemical criteria.